Engineering the surface atomic structure of FeVO4 nanocrystals for use as highly active and stable electrocatalysts for oxygen evolution. Issue 18 (25th April 2019) - Wang, Wei; Zhang, Yajun; Huang, Xiaojuan; Bi, Yingpu
Abstract : FeVO4 nanobelts bounded by 010 facets exhibit much higher OER activities and lower overpotential than nanosheets enclosed by 010 facets, which were mainly attributed to the favorable atomic arrangements of 010 facets with Fe–V dual-active sites and an open surface structure. Abstract : Here, we demonstrate the controlled construction of FeVO4 nanobelts and nanosheets with selectively exposed 010 and 001 facets, respectively. More importantly, the FeVO4 nanobelts exhibit more efficient electrocatalytic activities than the nanosheets, with a low overpotential of 240 mV (10 mA cm −2 ) and durability (36 h) towards the oxygen evolution reaction (OER). Further studies clearly reveal that the improved activity of FeVO4 nanobelts is mainly attributed to the open surface structure and favorable atomic arrangements of 010 facets, which assure rapid charge transfer and Fe–V dual-active sites for the OER.